92.4k views
4 votes
How do I do this equation?​

How do I do this equation?​-example-1
User JSN
by
6.0k points

2 Answers

3 votes

Answer:

x = -7 , -1

Explanation:

[x² + 6x + 8]/4x - 1/4x = -1/2

[x² + 6x + 8 - 1]/4x = -1/2

[x² + 6x + 7] = -1/2 × 4x

x² + 6x + 7 = -2x

x² + 6x + 7 + 2x = 0

x² + 8x + 7 = 0

x² + x + 7x + 7 = 0

x(x + 1) + 7(x + 1) = 0

(x + 7)(x + 1) = 0

x + 7 = 0 x = -7

x + 1 = 0 x = -1

x = -7 , -1

User Finisinfinitatis
by
6.4k points
4 votes

Answer: x= -1, -7

Explanation:

User Hafez
by
6.1k points